Model of Vocational Education Learning Format to Comply Hopefulness in Companies and Industries - Rompas, Parabelem T.D.; Sumual, Herry (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
The companies and industries were very demanding manpower not only must be prepared to work in accordance with their competence but also that very important of them was the work attitude should be good. In fact, currently it was not so because of any manpower that was when received as worker. The study presents the concept of vocational education learning format model that appropriate and comply hopefulness of companies and industries. The method used the literature review, interview, creation of the competency-based learning program of work in companies and industries. The results have shown that the model of learning format was vary and depending on the characteristics of the subject of course to be achieved and attitude learning applied in every learning. Implementation of learning format model should be supported by together from education leadership and head of companies and industries in achieving the goals and benefits together.